A basic investigation on low-energy ion irradiation effect on lives - Low-energy ion irradiation of naked DNA - L. D. Yu (2018)
Low-energy ions are everywhere, from arrivals of natural cosmic particles at the earth to biological and medical applications of manmade accelerator and plasma generated ions. When the low-energy ions irradiate biological cells, the basic effect is induction of mutation or killing of lives. Because of this effect, low-energy ion irradiation has widely been applied for mutation breeding and sterilization. However, some fundamentals involved in the applications are not yet well understood. Furthermore, biological effects from slow-down space particles and radiotherapy ions on genetic mutations are also not yet very clear. Some critical puzzles include whether the low-energy ion irradiation induced biological effect is a direct or indirect interaction consequence, what changes occur in DNA irradiated by low-energy ions, and what the lowest ion energy limit is to cause mutation. To look for answers, this investigation applies both experimental and computer simulation means, in which ions at energy from keV down to eV are used to bombard naked plasmid DNA, followed by checking DNA structure changes. In the experiment, nitrogen and argon ions at keV energy generated from low-energy ion accelerators or plasma bombarded naked plasmid DNA in vacuum to low fluences in orders of 1011-1013ions/cm2and the samples were analyzed using electrophoresis and sequencing. Results show that the low-energy ion irradiation of naked DNA can indeed cause DNA damage in the forms of single strand breakage, double strand breakage and multiple double strand breakage, which are the bases of mutation of biological organisms. Lighter nitrogen ions are found more effective in induction of mutation than heavier argon ions. Molecular dynamics simulation of ion bombardment of naked DNA reveals that ion interaction with DNA is not random but preferential. This presentation reports related details.